Estudio Y Diseño de un Sistema de Control de Acceso Vehicular para el Campus Universitario de la Universidad Nacional de Loja - Condoy Reyes, Karla Lucia (2020)
The purpose of this degree project was to design a vehicle access control system for the National University of Loja, which would allow proper control and monitoring of the number of vehicles entering the facilities, as well as recording their entry and exit, through a technical solution that meets all the requirements presented by the Administrative Management Department for future implementation. The design of this access control system covers two academic campuses of the National University of Loja, such as: Ciudadela Universitaria Guillermo Falconí Espinosa y Campus Facultad de Salud Humana. To carry out this project, firstly, the analysis and evaluation of the most used current electronic technologies in vehicle access controls was carried out, and it was determined that the appropriate technology to control the entrances and exits of the institution is the Automatic License Plate Recognition Technology (ANPR). In addition, in order to complement the aforementioned technology, the use of vehicle barriers is also planned in order to have a feasible and safe access control. Based on the technology chosen for vehicle access control, the communication network was designed to allow the integral connection of this system with the current data network of the National University of Loja, through the use of a fiber optics as a transmission medium. Finally, the necessary equipment for this project was selected, taking into account its functionality and a good cost-benefit ratio. From this, its analysis of unit prices is prepared to obtain the reference budget and a technical report as a reference for the future implementation of this vehicle access control system on the campus of the National University of Loja.